Developing and Validating Instrument for Online History Learning Oriented towards Historical Empathy based on the CIPP Evaluation - Labibatussolihah, Labibatussolihah; Adriani, Nour Muhammad; Fathiraini, Nurdiani (Universitas Negeri Malang, 2023)
The international crisis as the Covid-19 global health emergency has emphasized the need to strengthen social values such as empathy. Meanwhile, online learning during the pandemic created new challenges for teachers in instilling social values and norms, including in history subjects. This study aims to develop an evaluation instrument for historical learning oriented toward cultivating historical empathy. Using the CIPP framework from Stufflebeam, academics (lecturers) and education practitioners (teachers) developed a set of questionnaires and tested them on 259 high school students in Bandung. Some conclusions that can be drawn include (1) the existing instruments are acceptable based on standard factor analysis and Cronbach’s alpha >0.7; (2) teachers tend not to include the element of empathy in learning history; (3) the context (C) and process (P) aspects of history learning based on historical empathy are still low compared to the input (I) and product (P) aspects.